Determinants of Self-Esteem Among Breast Cancer Patients: A Literature Review - Deftiana, Azra; Budhiana, Johan; Huda, Akhmad (Jurnal Ragam Pengabdian, 2026)
Breast cancer patients often experience physical and psychological changes that may affect their self-esteem. Low self-esteem can influence treatment adherence, psychological well-being, and overall quality of life. This study aims to identify factors that influence self-esteem among breast cancer patients. The method used was a literature review following the PRISMA guidelines. Articles were searched from Google Scholar, PubMed, ScienceDirect, and Taylor & Francis Online, databases using the keywords “self-esteem”, “breast cancer patients”, and “determinants”. Articles published between 2020–2025 were included. From 3,470 identified articles, 9 studies met the inclusion criteria and were analyzed descriptively. The results show that self-esteem in breast cancer patients is influenced by several factors, including family support, body image, meaning of life, self-efficacy, and anxiety. Family support was consistently reported as a significant factor associated with higher self-esteem. These findings highlight the importance of psychosocial support in improving the psychological well-being of breast cancer patients.